Management Background, Intellectual Capital and the Financial Performance of Indonesian Banking (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2016)
This research aims to determine the effect of accounting education background, MBA education background, and the proportion of Chinese ethnic as well as intellectual capital measured by VAIC method on conventional banking financial performance in Indonesia. The population in this study is the entire conventional banking companies listed on Indonesia Stock Exchange that has been operating over the range of 2012-2015, so we get a sample totalling 29 companies. This research used Eviews 7 software to conduct panel data regression analysis. The results showed that accounting education background and Chinese ethnic are not significantly affecting financial performance. Meanwhile MBA education background and VAIC are significantly affecting financial performance (ROA).